Prevalence of Antimicrobial Resistance in Enterococci and Escherichia coli in Meat Chicken Flocks During a Production Cycle and Egg Layer Pullets During Rearing - Obeng, Akua Serwaah; Rickard, Heather; Ndi, Olasumbo; Sexton, Margaret; Barton , Mary (International Journal of Poultry Science, 2014)
Avian Pathogenic Escherichia coli (APEC) and some enterococci are important zoonotic pathogens associated with poultry and some human illnesses. This study was conducted to evaluate the phenotypic antibiotic resistance and resistance genes during the production cycle of healthy free-range meat chickens and egg layer pullets raised in two different controlled farms in South Australia, in particular to determine at which point in the production cycle birds become colonized with antibiotic resistant bacteria. Antibiotic resistance was investigated in faecal E. coli (206) and enterococcal (252) isolates by agar dilution and polymerase chain reaction. Southern hybridization was carried on plasmids from selected multi-resistant E. coli isolates to determine the location of resistance genes. Our results revealed that birds are colonized with resistant bacteria encoding various resistance genes from a very early age. Resistance to ampicillin and tetracycline (and associated resistance genes) were the most frequently detected resistances in E. coli isolates from egg layer pullets and free-range meat chickens. Phenotypically resistant enterococcal isolates from 3-5 days old chickens carried genetic determinants for resistance to tetracycline, bacitracin and tylosin. Whilst statistical analysis revealed there was no significant differences (p<0.05) with the phenotypic resistance observed in the E. coli and enterococcal isolates from meat chickens and egg layer pullets, a significant difference was observed in resistant E. coli isolates containing blaTEM and tet genes. This study demonstrates that newly hatched chicks are already colonized with resistant bacteria which persist through the production cycle and can potentially contaminate eggs and chicken carcasses. This study also confirms that poultry are a potential source of pathogenic E. coli strains.